Crosstalk among Epigenetic Pathways Regulates Neurogenesis - Jobe, Emily M.; McQuate, Andrea L.; Zhao, Xinyu (Frontiers in Neuroscience, 2012)
The process of neurogenesis, including neural stem cell proliferation, fate specification, young neuron migration, neuronal maturation, and functional integration into existing circuits, persists in restricted regions of the postnatal brain. Of the many endogenous mediators of postnatal neurogenesis, epigenetic pathways, such as components of DNA methylation and chromatin remodeling systems and non-coding RNA modulators, appear to play an integral role. Mounting evidence shows that such epigenetic factors form regulatory networks, which govern each step of postnatal neurogenesis. In this review, we explore the emerging role crosstalk among epigenetic proteins plays in regulating the entire process of postnatal and adult neurogenesis. We go on to explain how crosstalk between these pathways may serve to translate environmental cues into control of the neurogenic process.